"Love is also a lover of life": creatio ex nihilo and creaturely goodness. (25th March 2013) - Webster, John
Abstract Christian teaching about creation out of nothing appears to evacuate creatures of intrinsic worth. A theological‐spiritual response to this anxiety outlines the elements of the doctrine: (1) understanding creation requires the direction of intelligence by divine instruction; (2) God alone is cause of being to other beings, by his power, will and goodness; (3) the act of creation is ineffable, instantaneous, without movement, supereminent, and without material cause; (4) created things have being by divine gift; (5) the relation of creator and creatures is mixed, the creator not being constituted by creatures. Does this entail a metaphysics of creaturely privation in which creatures are permanently indigent? The creator is benevolent and, with no self‐interest, gives life, and so moves creatures to activity that the non‐reciprocal character of the creator‐creature relation is not malign but the principle of creaturely perfection.